ARTIFICIAL INTELLEGENCE DENGAN PEMBENTUKAN NILAI DAN KARAKTER DI BIDANG PENDIDIKAN - Mulianingsih, Ferani; Anwar, Khoirul; Shintasiwi, Fitri Amalia; Rahma, Anggi Jazilatur (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2020)
Artificial Intelligence with the Formation of Values and Character in the Field of Education. Artficial Intelligence is a branch of computer science that emphasizes the development of machine intelligence, thinking patterns and working like humans. For example, voice recognition, problem solving, learning and planning. AI is a branch of the digital literacy system that has a major role in the intelligence development process. In the field of education it also needs innovation efforts in learning media, and one of them is the application of AI. The purpose of this research is to improve the quality of student learning and to instill values and character while adapting to the AI system. The method used uses experimental methods to find out how adaptation and student responses to the base system in overcoming the problems that occur. AI makes it easy for students and students to support their studies in a visibility and comprehensive manner. Artificial Intelligence does create a student's mindset to be more critical and observant, but it will not completely guarantee good grades and character. So, there is a need for direct guidance and direction from educators coupled with the use of artificial intelligence-based features.